2023
DOI: 10.1073/pnas.2311667120
|View full text |Cite
|
Sign up to set email alerts
|

Recovering the susceptibility of antibiotic-resistant bacteria using photooxidative damage

Jennifer M. Soares,
Vladislav V. Yakovlev,
Kate C. Blanco
et al.

Abstract: Multidrug-resistant bacteria are one of the most serious threats to infection control. Few new antibiotics have been developed; however, the lack of an effective new mechanism of their action has worsened the situation. Photodynamic inactivation (PDI) can break antimicrobial resistance, since it potentiates the effect of antibiotics, and induces oxidative stress in microorganisms through the interaction of light with a photosensitizer. This paper addresses the application of PDI for increasing bacterial suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This approach enhances the efficacy of antibacterial treatments by leveraging the strengths of both PDI and antibiotics [27,[35][36][37]. We showed [26], in agreement with literature [34,36], that the order and number of each individual treatment sessions impact the inactivation of MRSA or E. coli, and found that PDI followed by antibiotic administration yielded the best results.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This approach enhances the efficacy of antibacterial treatments by leveraging the strengths of both PDI and antibiotics [27,[35][36][37]. We showed [26], in agreement with literature [34,36], that the order and number of each individual treatment sessions impact the inactivation of MRSA or E. coli, and found that PDI followed by antibiotic administration yielded the best results.…”
Section: Introductionsupporting
confidence: 86%
“…Despite this progress, it is difficult to completely eradicate bacteria present in infected tissues and avoid recurrence with PDI alone [10,[27][28][29][30][31][32]. Recent studies emphasized that the synergic combination of PDI with existing antibiotics is a more promising approach to tackle multi-resistant bacteria and delay antibiotic resistance [26,33,34]. This approach enhances the efficacy of antibacterial treatments by leveraging the strengths of both PDI and antibiotics [27,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…This damage can increase the bacteria's susceptibility to antimicrobial agents, potentially leading to changes in susceptibility through PDI, which we have previously demonstrated, but in this study, we evaluated different light dose conditions and intervals between cycles. [14] The clinical isolate of S. aureus was resistant to the antibiotics evaluated, with MIC values of 1024 µg/ml for AMO and 512 µg/ml for ERY and GEN, as shown in Figure 1.A, which shows the MIC over the five PDI cycles. The cut-off point defines that above the values obtained are classified as resistant bacteria, below the breakpoint the bacteria are classified as sensitive.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, employing sub-doses of PDI circles can improve the antibiotic susceptibility of multidrug-resistant strains. [13,14] But in addition to obtaining synergistic combinations, it is necessary to reduce the dosage of antimicrobials, which makes it possible to increase the expectation of using existing antibiotics, mitigating the scenarios of antibiotic failures, as demonstrated in this work.…”
Section: Introductionmentioning
confidence: 98%
“…APDT operates through production of reactive oxygen species (ROS) by photosensitizer (PS) molecules under light illumination. The main advantages of APDT are the lack of resistance development after exposure, selective binding to pathogens, local administration of a PS and localized irradiation with light, minimizing the side effects [1][2][3][4].…”
mentioning
confidence: 99%